Benchmark TPC-C aplicado em replicação máquina de estados - Serafim, Kayel Ludtke (2023)
The availability of a system can be impacted by failures or attacks that exploit its vulnerabilities. Increasingly, more people rely on available online systems on the Internet. To minimize downtime risks, State Machine Replication (SMR) is a common approach. SMR is an important strategy for providing highly available services. However, increasing capacity in SMR systems is challenging due to its deterministic model, which requires research efforts to improve its parallelism. Nevertheless, there is a lack of workloads to evaluate different SMR mechanisms according to common and representative criteria for classes of applications of interest. Based on this, important common aspects were identified in the context of online transactions, and the use of TPC-C, the Transaction Processing Performance Council’s benchmark C, this work proposes to evaluate SMRs. Its architecture for the SMR context is discussed and an implementation on a replication platform is provided. TPC-C performance results are presented for the classic SMR model. Additionally, a parallel SMR approach is discussed, and implemented with this workload, and the results obtained reported.